Research on Command Center Design for Districts and Cities in West Java - Rismayadi, Hilman; Wisnuadji, Sigit; Kusbandiah, Dian (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
This study examines the design of Command Centers for Regencies and Cities in West Java as a control and coordination center in handling emergency situations and decision making. The design of the Command Center includes various supporting facilities such as a reception area, main room, meeting room, equipment room, pantry, rest room, prayer room, and toilet, which are designed to support effective and efficient operations. Using advanced technology in visualization and telecommunications, this Command Center is expected to increase the capacity of local government response to crises that occur, by facilitating better communication and coordination between various stakeholders. This study also considers the specific needs of each region and compliance with applicable standards, so that the resulting design is not only functional but also adaptive to technological developments and future needs.